Hole transport material, hole transport layer, preparation method of hole transport material and hole transport layer, and perovskite cell

By using multiple Si-X bonds to form stable chemical bonds with substrate oxides in perovskite solar cells, combined with molecular layer deposition technology, the problem of poor binding ability between hole transport materials and substrates is solved. Improve the stability and photoelectric conversion efficiency of perovskite batteries.

CN119264175APending Publication Date: 2025-01-07SHANGHAI SHENGJIAN ENVIRONMENTAL SYST TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411395951.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The hole transport materials in existing perovskite solar cells have poor binding capabilities with substrates, resulting in weak interface stability and affecting the photoelectric conversion efficiency.

Method used

Multiple Si-X bonds are used to form a stable chemical bonded hole transport material, and the coverage density and stacking of the single molecular layer are accurately regulated through molecular layer deposition technology to form uniform and dense hole transport layer.

Benefits of technology

It improves the interface stability of the hole transport layer, enhances the stability and photoelectric conversion efficiency of perovskite batteries, avoids short circuits or increases series resistance, and improves voltage and filling performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264175A_ABST
    Figure CN119264175A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of perovskite cells, in particular to a hole transport material, a hole transport layer, a preparation method of the hole transport layer and a perovskite cell. The hole transport material disclosed by the invention has a general formula of X3Si-G-R, wherein X is selected from halogen, and G is selected from # imgabs0 # or a benzene ring; r is selected from a structure (I) or a structure (II). The hole transport material provided by the invention has a plurality of Si-X bonds which can form stable chemical bond combination with hydroxyl in a substrate oxide, and the hole transport material has saturated vapor pressure at a lower temperature and is suitable for preparing a trans-perovskite solar cell through molecular layer deposition; the hole transport material can improve the interface stability of the hole transport layer, so that the stability of the perovskite cell is improved, and the photoelectric conversion efficiency of the perovskite cell is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of perovskite cells, and in particular to a hole transport material, a hole transport layer and a preparation method thereof, and a perovskite cell. Background Art

[0002] The advantages of inverse perovskite solar cells (IPVSCs) include simple process, low-temperature film formation, low hysteresis, stability, and easy flexibility. They are suitable for compatibility with traditional crystalline silicon solar cells to realize stacked devices. Therefore, they have high commercial prospects and have attracted much attention.

[0003] Hole transport materials (HTM) in perovskite solar cells mainly include poly(p-phenylene vinylene), polythiophene, polysilane, triphenylmethane, etc. In recent years, researchers have been designing and developing low-cost, high-performance hole transport materials. Conventional hole transport materials have poor binding ability with the substrate, resulting in weak interface stability of the hole transport layer, which in turn affects the photoelectric conversion efficiency of perovskite solar cells.

[0004] Self-assembled materials have multiple advantages such as low cost, compatibility with flexible substrates, adjustable band gap, and high light transmittance, and are used in the research of preparing hole transport layers. However, the existing technology of using self-assembled materials to prepare hole transport layers has the defects of easy local formation of multi-molecular layers and poor film interface stability.

[0005] Therefore, how to obtain a hole transport material that can form a stable bond with the substrate and easily form a monomolecular film structure and improve the interface stability of the hole transport layer is crucial to promoting the development of perovskite solar cells.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] One object of the present invention is to provide a hole transport material having multiple Si-X bonds that can form stable chemical bonds with the -OH of the substrate oxide, thereby improving the interface stability of the hole transport layer, thereby facilitating the improvement of the stability of the perovskite battery and the improvement of its photoelectric conversion efficiency.

[0008] Another object of the present invention is to provide a method for preparing the hole transport material, which is simple and easy to implement.

[0009] Another object of the present invention is to provide a method for preparing a hole transport layer.

[0010] Another object of the present invention is to provide a hole transport layer.

[0011] Another object of the present invention is to provide a perovskite battery.

[0012] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0013] The hole transport material of the present invention has a general formula of X3Si-GR; in the general formula, X is a halogen; G is or benzene ring.

[0014] The group R is selected from structure (I) or structure (II):

[0015] The structure (I) is

[0016] The structure (II) is

[0017] ** in structure (I) and * in structure (II) respectively represent the binding sites with the G.

[0018] The hole transport material in the present invention has multiple Si-X bonds, which can form stable chemical bonds with the hydroxyl groups in the substrate oxide. It has a saturated vapor pressure at a relatively low temperature and is suitable for preparing inverse perovskite solar cells by molecular layer deposition. It can improve the interface stability of the hole transport layer, thereby improving the stability of the perovskite cell and improving its photoelectric conversion efficiency and safety.

[0019] The method for preparing the hole transport material as described above comprises the following steps:

[0020] The mixed system formed by the diphenylamine mother core source and / or the triphenylamine mother core source, the SiX source and the catalyst is heat-treated to obtain a hole transport material.

[0021] The preparation method of the hole transport material in the present invention is simple and easy. The obtained hole transport material has a saturated vapor pressure at a relatively low temperature. The multiple Si-X bonds in the hole transport material can form chemical bonds with the -OH of the substrate oxide to form stable multi-anchors, thereby improving the long-term stability of the interface.

[0022] The method for preparing the hole transport layer as described above comprises the following steps:

[0023] The hole transport material is deposited on the surface of a substrate having a polyhydroxy structure by molecular layer deposition to form a hole transport layer having a monomolecular layer.

[0024] The present invention makes full use of molecular layer deposition film-forming technology to accurately control the self-assembled molecular SAM-HTM to form a uniform monolayer film. The polyhalogenated SAMs hole transport material can be vaporized at a relatively low temperature, and chemical bonding occurs through a gaseous atmosphere to achieve precise control of the density and accumulation of the polyhalogenated SAM-HTM material single molecule covering the surface of the substrate oxide, and the precise control of the binding ability of the polyhalogenated SAMs material monolayer and the substrate oxide to avoid voids, thereby avoiding short circuits in perovskite batteries or increasing series resistance, which is beneficial to the voltage and filling of perovskite batteries.

[0025] A hole transport layer is prepared by the hole transport layer preparation method.

[0026] In the hole transport layer of the present invention, the anchoring group of the polyhalogenated SAM hole transport material can form a chemical bond with the -OH of the substrate oxide to form a uniform, dense, and ordered monolayer with a suitable surface coverage density and stacking to avoid voids, short circuits of the perovskite battery, or increase in series resistance. The charge selectivity can be improved by generating an interface dipole moment to induce hole extraction, thereby improving the voltage and filling performance of the perovskite battery.

[0027] A perovskite battery comprises the hole transport layer.

[0028] The perovskite battery prepared by the hole transport material of the present invention has excellent stability, high photoelectric conversion efficiency and good safety performance.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) The hole transport material of the present invention uses diphenylamine / triphenylamine units with simple structure, low cost and good hole transport properties as molecular matrix, and enhances the hole transport and interface passivation properties of the material by regulating the functional groups at the contact interface between diphenylamine / triphenylamine and perovskite, reduces the energy loss at the interface, enhances the molecular stacking and hole transport performance with straight chain or benzene ring, uses halogenated silicon as anchoring group, realizes the self-assembly of SAM-HTL on the substrate surface, reduces the material consumption, and improves the interface stability.

[0031] (2) The present invention makes full use of the film-forming technology of molecular layer deposition (MLD) to precisely control the self-assembled molecular SAM-HTM to form a uniform monolayer film. The polyhalogenated SAMs hole transport material can be vaporized at a relatively low temperature, and chemical bonding occurs through the gaseous atmosphere to precisely control the density and stacking of the polyhalogenated SAM-HTM material single molecule on the surface of the substrate oxide. The bonding ability between the polyhalogenated SAMs material monolayer and the substrate oxide is precisely controlled to avoid voids, thereby avoiding short circuits in the perovskite battery or increasing the series resistance, which is beneficial to the voltage and filling of the perovskite battery.

[0032] (3) The perovskite battery prepared by the hole transport material of the present invention has excellent stability, high photoelectric conversion efficiency and high safety performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0034] Figure 1 FIG. 4 is a diagram of the MLD deposition mechanism of the hole transport layer according to an embodiment of the present invention. DETAILED DESCRIPTION

[0035] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0036] According to one aspect of the present invention, the present invention relates to a hole transport material having the following general formula:

[0037] X3Si-GR.

[0038] Wherein, X is selected from halogen; G is selected from or a benzene ring. n is a positive integer of 1 to 20, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20.

[0039] R is selected from the following structure (I) or structure (II):

[0040]

[0041] ** in structure (I) and * in structure (II) respectively represent the bonding sites with the above-mentioned G.

[0042] The hole transport material of the present invention uses a diphenylamine unit with a simple structure, low cost and good hole transport properties as a molecular matrix, and controls the functional groups at the contact interface between diphenylamine and perovskite to enhance the hole transport and interface passivation properties of the material, reduce energy loss at the interface, enhance molecular stacking and hole transport performance with a straight chain or a benzene ring, and avoid high synthesis difficulty with a proper carbon chain length. Halogenated silicon / phosphorus is used as an anchoring group to achieve self-assembly of SAM-HTL on the surface of a substrate, reduce material usage, and improve interface stability, thereby facilitating the improvement of the stability of the perovskite battery and the improvement of its photoelectric conversion efficiency.

[0043] In some embodiments, X is selected from at least one of F, Cl and Br. At least one of F, Cl and Br forms an anchoring group with silicon, which can realize the self-assembly of SAM-HTL on the substrate surface, reduce the amount of materials used and improve the interface stability. X is preferably Cl, and the anchoring effect of chlorosilicon is better, which is more conducive to improving the interface stability.

[0044] In some embodiments, R1 and R2 in structure (I) and R1 and R2 in structure (II) are each independently H, I, Br, methyl (Me), methoxy (MeO), phenyl (Ph), S-containing heterocycle, N-containing heterocycle or O-containing heterocycle. R1 and R2 in structure (I) may be the same or different, and R1 and R2 in structure (II) may be the same or different.

[0045] In some embodiments, when X is a Cl atom, G is selected from R is selected from structure (I), and R1 and R2 in structure (I) are both methoxy groups, and the structural formula of the hole transport material is:

[0046]

[0047] In some embodiments, when X is a Cl atom, G is selected from R is selected from structure (I), and R1 and R2 are different, R1 is an O-containing heterocyclic ring, and R2 is an S-containing heterocyclic ring. The structural formula of the hole transport material is:

[0048]

[0049] In some embodiments, when X is a Cl atom, G is selected from And R is selected from structure (II), and R1 and R2 are both methyl groups, and the structural formula of the hole transport material is:

[0050]

[0051] In some embodiments, when X is a Cl atom, G is selected from R is selected from structure (II), and R1 and R2 are different, R1 is a heterocyclic ring containing S, and R2 is a heterocyclic ring containing O. The structural formula of the hole transport material is:

[0052]

[0053] In some embodiments, the structural formula of the hole transport material includes any of the following:

[0054]

[0055]

[0056]

[0057] According to another aspect of the present invention, the present invention also relates to a method for preparing the above hole transport material, comprising the following steps:

[0058] The mixed system of the diphenylamine mother core source and / or the triphenylamine mother core source, the SiX source and the catalyst is heat-treated to obtain a hole transport material.

[0059] The preparation method of the hole transport material of the present invention is simple and easy. The obtained hole transport material has a saturated vapor pressure at a relatively low temperature. Multiple Si-X bonds in the hole transport material can form chemical bonds (Si-O bonds) with -OH of the substrate oxide to form stable multi-anchors, which is beneficial to improving the long-term stability of the interface.

[0060] In some embodiments, the diphenylamine parent core source has the following structural formula:

[0061] Wherein, M1 represents a carbon chain with 1 to 20 carbon atoms or a benzene ring structure, A1 represents a halogen, and the halogen includes Cl or Br; R3 and R4 are each independently H, I, Br, methyl, methoxy, phenyl, S-containing heterocycle, N-containing heterocycle or O-containing heterocycle.

[0062] In some embodiments, the triphenylamine parent core source has the following structural formula:

[0063] Wherein, M2 represents a carbon chain with 1 to 20 carbon atoms or a benzene ring structure, A2 represents a halogen, and the halogen includes Cl or Br; R5 and R6 are each independently H, I, Br, methyl, methoxy, phenyl, S-containing heterocycle, N-containing heterocycle or O-containing heterocycle.

[0064] In the above-mentioned diphenylamine mother core source and triphenylamine mother core source, the carbon chain with 1 to 20 carbon atoms refers to: n is 1 to 20, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20.

[0065] In some embodiments, the diphenylamine parent core source and the triphenylamine parent core source include the following structures:

[0066] SM1: SM2:

[0067] SM3: SM4:

[0068] SM5: SM6:

[0069] In some embodiments, the SiX source includes trichlorosilane (SiHCl3). A suitable SiX source can ensure that the parent core fully reacts, improve the utilization rate of the parent core, form a specific anchoring group, make the hole transport material have a better anchoring effect, and improve the interface stability of the hole transport layer.

[0070] In some embodiments, the molar ratio of the diphenylamine parent core source or the triphenylamine parent core source to the SiX source is 1:(2-4), such as 1:2, 1:3 or 1:4, etc. The suitable material molar ratio of the present invention ensures that the materials react fully and efficiently to obtain a hole transport material with high purity and high yield.

[0071] In some embodiments, the temperature of the heat treatment is 130 to 180°C, for example, 130°C, 133°C, 135°C, 137°C, 140°C, 143°C, 145°C, 147°C, 150°C, 153°C, 155°C, 157°C, or 160°C, and the time of the heat treatment is 1 to 3 hours, including but not limited to 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, etc. The heat treatment of the present invention adopts the above-mentioned suitable temperature and time to ensure that the material is fully reacted to obtain a high-yield, high-purity hole transport material, which is beneficial to ensure the hole transport and interface passivation characteristics of the final hole transport material, reduce energy loss at the interface, and help improve interface stability. The temperature of the heat treatment is less than 130°C or greater than 180°C, which is not conducive to the full reaction of the material and affects the yield and purity of the hole transport material.

[0072] In some embodiments, the catalyst includes at least one of tetrabutylphosphine chloride, tetraethylammonium chloride and triphenylphosphine rhodium chloride. The use of the above catalyst is conducive to increasing the reaction rate and allowing the materials to react fully.

[0073] According to another aspect of the present invention, the present invention also relates to a method for preparing a hole transport layer, comprising the following steps:

[0074] The hole transport material is deposited on the surface of the substrate by molecular layer deposition. The surface of the substrate has a polyhydroxy structure to form a hole transport layer with a monomolecular layer.

[0075] The present invention makes full use of the molecular layer deposition film-forming technology to accurately control the self-assembled molecular SAM-HTM to form a uniform monolayer film. The polyhalogenated SAMs hole transport material can be vaporized at a relatively low temperature, and chemical bonding occurs through the gaseous atmosphere to achieve precise control of the density and accumulation of the polyhalogenated SAM-HTM material single molecule on the surface of the substrate oxide, and the precise control of the binding ability of the polyhalogenated SAMs material monolayer and the substrate oxide to avoid voids, thereby avoiding short circuits of perovskite cells or increasing series resistance, which is beneficial to the voltage and filling of perovskite cells. The MLD deposition mechanism diagram of the hole transport layer of the present invention is shown in the figure below: Figure 1 shown.

[0076] MLD is an advanced organic polymer film and organic-inorganic hybrid film preparation technology. Compared with the traditional organic polymer film deposition process (spin coating, thermal evaporation), the film thickness is precisely controllable, the thickness is more uniform, and the shape retention is better. MLD deposition principle: MLD pulses the gaseous molecules of the hole transport material by plasma or heating, so that the anchoring groups in the hole material and the -OH on the surface of the substrate are self-assembled and bonded until saturation, forming a monomolecular film layer of the hole transport layer.

[0077] In some embodiments, the substrate is pretreated, and the pretreatment includes: ultrasonically treating the substrate to be treated in water, glass cleaning liquid, acetone and isopropanol in sequence, and then treating with ozone after drying, wherein the ultrasonic treatment time is 10 to 20 minutes, and the ozone treatment time is 10 to 20 minutes. In the present invention, the substrate to be treated is ultrasonically treated in water, glass cleaning liquid, acetone and isopropanol to ensure the cleanliness of the substrate surface. Ozone treatment, i.e., ozone atmosphere, reacts with the substrate surface to generate an oxygen-rich layer, so that the surface of the substrate has a rich hydroxyl content.

[0078] In some embodiments, the plasma radio frequency of the molecular layer deposition method is 10 to 30 KHz, and the deposition time is 2 to 5 seconds. The present invention adopts appropriate molecular layer deposition conditions, that is, the plasma of the MLD is at a suitable frequency to obtain pulsed SAM-HTM gaseous molecules, and accurately controls the gaseous molecules to be deposited on the transparent conductive glass ITO, completes the bonding of the anchoring groups of the self-assembled molecules with the hydroxyl groups on the transparent conductive glass ITO, and after saturation, a SAM-HTM film with only one molecular layer is obtained.

[0079] According to another aspect of the present invention, the present invention also relates to a hole transport layer prepared by the above method for preparing a hole transport layer.

[0080] In the hole transport layer of the present invention, the multiple Si-X bonds of the polyhalogenated SAM hole transport material can form O-Si chemical bonds with the -OH of the substrate oxide to form stable multi-anchors. The hole transport material is a single molecular layer, that is, it has a suitable surface coverage density and stacking, avoids multiple molecular layers, avoids voids, thereby avoiding short circuits of perovskite batteries or increasing series resistance, and improving the voltage and filling of perovskite batteries.

[0081] According to another aspect of the present invention, the present invention also relates to a perovskite cell, comprising a hole transport layer.

[0082] The perovskite battery of the present invention has good stability and high photoelectric conversion efficiency.

[0083] In some embodiments, the perovskite battery further comprises a perovskite layer, an electron transport layer and an electrode layer; the hole transport layer is away from the surface of the substrate and the perovskite layer, the electron transport layer and the electrode layer are stacked in sequence. In some embodiments, the perovskite layer, the electron transport layer and the electrode layer are all conventional layer structures, and the perovskite layer may include Cs 0.2 FA 0.8 Pb(I 0.6 Br 0.4 )3, FA represents fluoroformamidine. The electron transport layer may be a composite layer of C60 and tin oxide. The electrode layer includes at least one of Ag and Cu.

[0084] In one embodiment, a method for preparing a perovskite battery comprises the following steps:

[0085] (1) The ITO glass substrate was ultrasonically treated in deionized water, glass cleaning solution, acetone and isopropanol for 15 minutes in sequence, and then dried (purged) with dry compressed air. The dried ITO glass was treated with ozone for 15 minutes to obtain a substrate with abundant hydroxyl groups on the surface.

[0086] (2) The processed substrate is placed in an enhanced plasma molecular deposition device, a small amount of hole transport material is added to the filler cavity, and then the plasma radio frequency is adjusted to 10 to 30 kHz. After pulsing steam for 2 to 5 seconds, it is switched to a cleaning mode to purge and remove excess hole transport material to obtain a monolayer hole transport layer.

[0087] (3) Spin-coating the perovskite solution onto the surface of the hole transport layer, thermally annealing at 90-110° C. for 3-6 min, and cooling to obtain a perovskite layer.

[0088] (4) 10 to 25 nm of C60 is evaporated on the surface of the perovskite layer, and then 5 to 30 nm of tin oxide is deposited by an atomic deposition device to obtain an electron transport layer.

[0089] (5) A layer of Ag with a thickness of 50 to 200 nm is vacuum evaporated on the surface of the electron transport layer as an electrode layer, thereby completing the preparation of the perovskite solar cell device.

[0090] The following is further explained in conjunction with specific embodiments and comparative examples.

[0091] Example 1

[0092] A method for preparing a hole transport material comprises the following steps:

[0093] The triphenylamine core source SM1 and trichlorosilane were mixed in a molar ratio of 1:3, and tetrabutylphosphine chloride was used as a catalyst. The mixture was reacted at 150°C for 2 hours. The resulting mixed system was distilled to obtain a hole transport material, which was recorded as SAM-TPA1.

[0094] The reaction formula is as follows:

[0095]

[0096] The hole transport material SAM-TPA1 obtained in this embodiment is used to prepare a perovskite cell, comprising the following steps:

[0097] (1) The ITO glass substrate was ultrasonically treated in deionized water, glass cleaning solution, acetone and isopropanol for 15 minutes in sequence, and then dried with dry compressed air. The dried ITO glass was treated with ozone for 15 minutes to obtain a substrate with abundant hydroxyl groups on the surface.

[0098] (2) Place the processed substrate in an enhanced plasma molecular deposition device, add an appropriate amount of hole transport material SAM-TPA1 into the filling chamber, then adjust the plasma RF frequency to 15 kHz, pulse steam for 2 seconds, and switch to the cleaning mode after the deposition is completed to purge and remove excess SAM-TPA1 to obtain a monolayer hole transport layer.

[0099] (3) 1.5M Cs 0.2 FA 0.8 Pb(I 0.6 Br 0.4 )3 The perovskite solution (solvent is dimethylformamide DMF) is spin-coated onto the surface of the hole transport layer, thermally annealed at 100°C for 5 minutes, and then cooled to obtain a perovskite layer.

[0100] (4) 20 nm of C60 is evaporated on the surface of the perovskite layer, and then 20 nm of tin oxide is deposited by an atomic deposition device to obtain an electron transport layer.

[0101] (5) Vacuum evaporate an 80nm layer of Ag as an electrode layer on the surface of the electron transport layer to complete the preparation of the perovskite solar cell device. The effective area of ​​the device is 4mm 2 .

[0102] Example 2

[0103] A method for preparing a hole transport material comprises the following steps:

[0104] The triphenylamine core source SM2 and trichlorosilane were mixed in a molar ratio of 1:3, and tetrabutylphosphine chloride was used as a catalyst. The mixture was reacted at 140°C for 3 hours. The resulting mixed system was distilled to obtain a hole transport material, which was recorded as SAM-TPA2.

[0105] The reaction formula is as follows:

[0106]

[0107] The hole transport material SAM-TPA2 obtained in this embodiment is used to prepare a perovskite cell, comprising the following steps:

[0108] (1) The ITO glass substrate was ultrasonically treated in deionized water, glass cleaning solution, acetone and isopropanol for 15 minutes in sequence, and then dried with dry compressed air. The dried ITO glass was treated with ozone for 15 minutes to obtain a substrate with abundant hydroxyl groups on the surface.

[0109] (2) The processed substrate is placed in an enhanced plasma molecular deposition device, a small amount of hole transport material SAM-TPA2 is added to the filling cavity, and then the plasma RF frequency is adjusted to 15 kHz. After pulse steam for 2 seconds, it is switched to the cleaning mode to purge and remove excess SAM-TPA2 to obtain a monolayer hole transport layer.

[0110] (3) 1.5M Cs 0.2 FA 0.8 Pb(I 0.6 Br 0.4 )3 The perovskite solution (solvent is dimethylformamide DMF) is spin-coated onto the surface of the hole transport layer, thermally annealed at 100°C for 5 minutes, and then cooled to obtain a perovskite layer.

[0111] (4) 20 nm of C60 is evaporated on the surface of the perovskite layer, and then 20 nm of tin oxide is deposited by an atomic deposition device to obtain an electron transport layer.

[0112] (5) A 70nm Ag layer was vacuum evaporated on the surface of the electron transport layer as an electrode layer to complete the preparation of the perovskite solar cell device. The effective area of ​​the device was 4mm 2 .

[0113] Example 3

[0114] A method for preparing a hole transport material comprises the following steps:

[0115] The diphenylamine core source SM3 and trichlorosilane were mixed in a molar ratio of 1:4, and tetrabutylphosphine chloride was used as a catalyst. The mixture was reacted at 150°C for 3 hours. The resulting mixed system was distilled to obtain a hole transport material, which was recorded as SAM-TPA3.

[0116] The reaction formula is as follows:

[0117]

[0118] The hole transport material SAM-TPA3 obtained in this embodiment is used to prepare a perovskite cell, comprising the following steps:

[0119] (1) The ITO glass substrate was ultrasonically treated in deionized water, glass cleaning solution, acetone and isopropanol for 15 minutes in sequence, and then dried with dry compressed air. The dried ITO glass was treated with ozone for 15 minutes to obtain a substrate with abundant hydroxyl groups on the surface.

[0120] (2) The processed substrate is placed in an enhanced plasma molecular deposition device, a small amount of hole transport material SAM-TPA3 is added to the filling cavity, and then the plasma RF frequency is adjusted to 15 kHz. After 2 seconds of pulse steam, it is switched to the cleaning mode to purge and remove excess SAM-TPA3 to obtain a monolayer hole transport layer.

[0121] (3) 1.5M Cs 0.2 FA 0.8 Pb(I 0.6 Br 0.4 )3 The perovskite solution (solvent is dimethylformamide DMF) is spin-coated onto the surface of the hole transport layer, thermally annealed at 100°C for 5 minutes, and then cooled to obtain a perovskite layer.

[0122] (4) 20 nm of C60 is evaporated on the surface of the perovskite layer, and then 20 nm of tin oxide is deposited by an atomic deposition device to obtain an electron transport layer.

[0123] (5) A 90nm Ag layer was vacuum evaporated on the surface of the electron transport layer as an electrode layer to complete the preparation of the perovskite solar cell device. The effective area of ​​the device was 4mm 2 .

[0124] Example 4

[0125] A method for preparing a hole transport material comprises the following steps:

[0126] The diphenylamine core source SM4 and trichlorosilane were mixed in a molar ratio of 1:3, and tetrabutylphosphine chloride was used as a catalyst. The mixture was reacted at 160°C for 2 hours. The resulting mixed system was distilled to obtain a hole transport material, which was recorded as SAM-TPA4.

[0127] The reaction formula is as follows:

[0128]

[0129] The hole transport material SAM-TPA4 obtained in this embodiment is used to prepare a perovskite cell, comprising the following steps:

[0130] (1) The ITO glass substrate was ultrasonically treated in deionized water, glass cleaning solution, acetone and isopropanol for 15 minutes in sequence, and then dried with dry compressed air. The dried ITO glass was treated with ozone for 15 minutes to obtain a substrate with abundant hydroxyl groups on the surface.

[0131] (2) The processed substrate is placed in an enhanced plasma molecular deposition device, a small amount of hole transport material SAM-TPA4 is added to the filling cavity, and then the plasma RF frequency is adjusted to 15 kHz. After 2 seconds of pulse steam, it is switched to the cleaning mode to purge and remove excess SAM-TPA4 to obtain a monolayer hole transport layer.

[0132] (3) 1.5M Cs 0.2 FA 0.8 Pb(I 0.6 Br 0.4 )3 The perovskite solution (solvent is dimethylformamide DMF) is spin-coated onto the surface of the hole transport layer, thermally annealed at 100°C for 5 minutes, and then cooled to obtain a perovskite layer.

[0133] (4) 20 nm of C60 is evaporated on the surface of the perovskite layer, and then 20 nm of tin oxide is deposited by an atomic deposition device to obtain an electron transport layer.

[0134] (5) Vacuum evaporate a layer of 80nm Cu on the surface of the electron transport layer as an electrode layer to complete the preparation of the perovskite solar cell device. The effective area of ​​the device is 4mm 2 .

[0135] Example 5

[0136] A method for preparing a hole transport material comprises the following steps:

[0137] The triphenylamine core source SM5 and trichlorosilane were mixed in a molar ratio of 1:2, and tetrabutylphosphine chloride was used as a catalyst. The mixture was reacted at 150°C for 4 hours. The resulting mixed system was distilled to obtain a hole transport material, which was recorded as SAM-TPA5.

[0138] The reaction formula is as follows:

[0139]

[0140] The hole transport material SAM-TPA1 obtained in this embodiment is used to prepare a perovskite cell, comprising the following steps:

[0141] (1) The ITO glass substrate was ultrasonically treated in deionized water, glass cleaning solution, acetone and isopropanol for 15 minutes in sequence, and then dried with dry compressed air. The dried ITO glass was treated with ozone for 15 minutes to obtain a substrate with abundant hydroxyl groups on the surface.

[0142] (2) The processed substrate is placed in an enhanced plasma molecular deposition device, and an appropriate amount of hole transport material SAM-TPA5 is added to the filling cavity. Then, the plasma RF frequency is adjusted to 15 kHz, and the pulse steam is used for 2 seconds. After the deposition is completed, it is switched to the cleaning mode to purge and remove the excess SAM-TPA5 to obtain a monolayer hole transport layer.

[0143] (3) 1.5M Cs 0.2 FA 0.8 Pb(I 0.6 Br 0.4 )3 The perovskite solution (solvent is dimethylformamide DMF) is spin-coated onto the surface of the hole transport layer, thermally annealed at 100°C for 5 minutes, and then cooled to obtain a perovskite layer.

[0144] (4) 20 nm of C60 is evaporated on the surface of the perovskite layer, and then 20 nm of tin oxide is deposited by an atomic deposition device to obtain an electron transport layer.

[0145] (5) Vacuum evaporate an 80nm layer of Ag as an electrode layer on the surface of the electron transport layer to complete the preparation of the perovskite solar cell device. The effective area of ​​the device is 4mm 2 .

[0146] Example 6

[0147] A method for preparing a hole transport material comprises the following steps:

[0148] The triphenylamine core source SM5 and trichlorosilane were mixed in a molar ratio of 1:4, and tetrabutylphosphine chloride was used as a catalyst. The mixture was reacted at 140°C for 3 hours. The resulting mixed system was distilled to obtain a hole transport material, which was recorded as SAM-TPA6.

[0149] The reaction formula is as follows:

[0150]

[0151] The hole transport material SAM-TPA6 obtained in this embodiment is used to prepare a perovskite cell, comprising the following steps:

[0152] (1) The ITO glass substrate was ultrasonically treated in deionized water, glass cleaning solution, acetone and isopropanol for 15 minutes in sequence, and then dried with dry compressed air. The dried ITO glass was treated with ozone for 15 minutes to obtain a substrate with abundant hydroxyl groups on the surface.

[0153] (2) Place the processed substrate in an enhanced plasma molecular deposition device, add an appropriate amount of hole transport material SAM-TPA6 into the filling cavity, then adjust the plasma RF frequency to 15 kHz, pulse steam for 2 seconds, and switch to the cleaning mode after the deposition is completed to purge and remove excess SAM-TPA6 to obtain a monolayer hole transport layer.

[0154] (3) 1.5M Cs 0.2 FA 0.8 Pb(I 0.6 Br 0.4 )3 The perovskite solution (solvent is dimethylformamide DMF) is spin-coated onto the surface of the hole transport layer, thermally annealed at 100°C for 5 minutes, and then cooled to obtain a perovskite layer.

[0155] (4) 20 nm of C60 is evaporated on the surface of the perovskite layer, and then 20 nm of tin oxide is deposited by an atomic deposition device to obtain an electron transport layer.

[0156] (5) A 70nm Ag layer was vacuum evaporated on the surface of the electron transport layer as an electrode layer to complete the preparation of the perovskite solar cell device. The effective area of ​​the device was 4mm 2 .

[0157] Comparative Example 1

[0158] In this comparative example, MeO-2PACz ([2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid) was used as a hole transport material, and a self-assembled monolayer was prepared by spin coating to prepare a perovskite solar cell, which specifically includes the following steps:

[0159] The ITO glass substrate was ultrasonically treated in deionized water, glass cleaning solution, acetone and isopropanol for 15 minutes, then dried with dry compressed air, and the dried ITO glass was treated with ozone for 15 minutes to obtain a substrate. MeO-2PACz was prepared into an ethanol solution with a concentration of 1 mg / mL, and after spin coating on the surface of the substrate, the excess MeO-2PACz on the surface was cleaned with ethanol, and thermally annealed at 100°C for 10 minutes.

[0160] 1.5M Cs0.2 FA 0.8 Pb(I 0.6 Br 0.4 )3 The perovskite solution was spin-coated onto the surface of the hole transport layer, and then thermally annealed at 100°C for 5 minutes. After cooling, a perovskite layer was obtained. 20nm of C60 and 20nm of tin oxide were deposited on the surface of the perovskite layer in sequence to obtain an electron transport layer. An 80nm layer of Ag was vacuum-evaporated on the surface of the electron transport layer as an electrode layer, thereby completing the preparation of the perovskite solar cell device. The effective area of ​​the device was 4mm 2 .

[0161] Experimental example

[0162] Use a xenon lamp solar simulator and test the light source intensity to be AM1.5G, 100mW / cm 2 The performance parameters of the batteries in the embodiments and comparative examples were tested under light: open circuit voltage (Voc), short circuit current density (Jsc), fill factor (FF), and photoelectric conversion efficiency (PCE).

[0163] The performance test results of perovskite cells are shown in Table 1.

[0164] Table 1 Performance test results of perovskite cells

[0165] Group SAM-HTM Film forming method Voc(V) <![CDATA[Jsc(mA / cm 2 )]]> FF(%) PCE(%) Example 1 SAM-TPA1 MLD 1.15 25.15 80.13 22.82 Example 2 SAM-TPA2 MLD 1.17 23.31 80.36 23.34 Example 3 SAM-TPA3 MLD 1.16 24.26 79.24 21.49 Example 4 SAM-TPA4 MLD 1.17 25.24 78.49 22.66 Example 5 SAM-TPA5 MLD 1.14 24.42 76.38 21.49 Example 6 SAM-TPA6 MLD 1.15 25.08 77.57 23.23 Comparative Example 1 MeO-2PACz Spin coating 1.11 23.19 76.93 19.12

[0166] As can be seen from Table 1, the hole transport materials obtained in various embodiments of the present invention are used to prepare a monolayer hole transport layer by molecular layer deposition to obtain a perovskite cell. The photoelectric conversion rate of the perovskite cell is improved compared with the photoelectric conversion rate of the cell prepared by the existing conventional hole transport materials.

[0167] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A hole transport material, characterized in that: The hole transport material has the following general formula: X3Si—G—R; Wherein, X is selected from halogen; G is selected from or benzene ring; R is selected from the following structure (I) or structure (II): ** in the structure (I) and * in the structure (II) respectively represent the connection sites with the G.

2. The hole transport material according to claim 1, characterized in that ,, including at least one of the following features (1) to (4): (1) n is an integer from 1 to 20; (2) X is selected from at least one of F, Cl and Br; (3) R1 and R2 in the structure (I) and R1 and R2 in the structure (II) are each independently H, I, Br, methyl, methoxy, phenyl, S-containing heterocyclic ring, N-containing heterocyclic ring or O-containing heterocyclic ring; (4) The structural formula of the hole transport material includes any one of the following:

3. A method for preparing a hole transport material according to any one of claims 1 to 2, characterized in that: The following steps are involved: The mixed system of the diphenylamine mother core source and / or the triphenylamine mother core source, the SiX source and the catalyst is heat-treated to obtain a hole transport material.

4. The method for preparing a hole transport material according to claim 3, characterized in that: Contains at least one of the following features (1) to (5): (1) The diphenylamine parent core source has the following general formula: Wherein, M1 represents a carbon chain with 1 to 20 carbon atoms or a benzene ring structure, A1 represents a halogen; R3 and R4 are each independently H, I, Br, methyl, methoxy, phenyl, S-containing heterocycle, N-containing heterocycle or O-containing heterocycle; (2) The triphenylamine parent core source has the following general formula: Wherein, M2 represents a carbon chain with 1 to 20 carbon atoms or a benzene ring structure, A2 represents a halogen, and R5 and R6 are each independently H, I, Br, methyl, methoxy, phenyl, S-containing heterocycle, N-containing heterocycle or O-containing heterocycle; (3) The SiX source includes trichlorosilane; (4) The molar ratio of the diphenylamine mother core source or the triphenylamine mother core source to the SiX source is 1:(2-4); (5) The temperature of the heat treatment is 130 to 180° C., and the time of the heat treatment is 1 to 3 hours.

5. A method for preparing a hole transport layer, characterized in that: The following steps are involved: The hole transport material described in claim 1 or 2 is deposited on the surface of a substrate having a polyhydroxy structure by molecular layer deposition to form a hole transport layer having a monomolecular layer.

6. The method for preparing a hole transport layer according to claim 5, characterized in that: The substrate is pretreated, and the pretreatment includes: ultrasonically treating the substrate to be treated in water, glass cleaning liquid, acetone and isopropanol in sequence, and then treating it with ozone after drying. The ultrasonic treatment time is 10 to 20 minutes, and the ozone treatment time is 10 to 20 minutes.

7. The method for preparing a hole transport layer according to claim 5, characterized in that: The plasma radio frequency frequency of the molecular layer deposition method is 10 to 30 KHz, and the deposition time is 2 to 5 seconds.

8. A hole transport layer, characterized in that: The hole transport layer is prepared by the method for preparing the hole transport layer according to any one of claims 5 to 7.

9. A perovskite battery, characterized in that: The method comprises the hole transport layer as claimed in claim 8.

10. The perovskite battery according to claim 9, characterized in that: The perovskite battery further includes a perovskite layer, an electron transport layer and an electrode layer; the hole transport layer is arranged to stack the perovskite layer, the electron transport layer and the electrode layer in sequence away from the surface of the substrate.

Citation Information

Cited By

  • TCO conductive glass and preparation method thereof

    CN122444435A